CSF Tryptophan in Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs)
The levels of tryptophan (TRP) metabolites in the CSF of 8 patients with infantile spasms are reported from the Department of Pediatrics, St. Marianna University School of Medicine, Kawasaki 213, Japan.